PENGEMBANGAN SUMBERDAYA APARATUR DALAM PENINGKATAN KINERJA PADA KANTOR KEARSIPAN DAN PERPUSTAKAAN KOTA TERNATE - Abdullah, Abjan (HOLISTIK, Journal Of Social and Culture, 2013)
Human resource development, as the man power having animportant role to increase performance staff. One of the important factor is which related to the demand to doing competence improvement of staff resources as the actions or effort to develop or improve knowledge ability, skill, and aparatur attitude in executing duty / each work through training and education. But not actually. With this research the researcher wish to know aparatur resources development in improving performance indeeply through a research at Archives and Library office of Ternate City. The result of research is seems that most of the staff have followed training and education but staff performance at Archives and Library office of Ternate City are not maximal yet. So that, its’ needed aparatur resources development are more intensified and orienting to attitude development and staff behavior.Keywords: human resource, competence, performance